Advances in the Additive Manufacturing of Superalloys - Antonio del Bosque; Pablo Fernández-Arias; Diego Vergara (Journal of Manufacturing and Materials Processing)
This study presents a bibliometric analysis of the evolution and research trends in the additive manufacturing (AM) of superalloys over the last decade (2015–2025). The review follows a structured methodology based on the PRISMA 2020 protocol, utilizing data from the Scopus and Web of Science (WoS) databases. Particular attention is devoted to the intricate process–structure–property relationships and the specific behavioral trends associated with different superalloy families, namely Ni-based, Co-based, and Fe–Ni-based systems. The findings reveal a substantial growth in scientific output, with the United States and China leading contributions and an increasing trend in international collaboration. Key research areas include process optimization, microstructural evolution and control, mechanical property assessment, and defect minimization. The study highlights the pivotal role of technologies such as laser powder bed fusion, electron beam melting, and directed energy deposition in the fabrication of high-performance components. Additionally, emerging trends point to the integration of machine learning and artificial intelligence for real-time quality monitoring and manufacturing parameter optimization. Despite these advancements, challenges such as anisotropic properties, porosity issues, and process sustainability remain critical for both industrial applications and future academic research in superalloys.